Innovative COVID-19 diagnostics and testing strategies in Italy, Denmark, UK, Israel and Sweden: a comparative analysis including tests, incidence and mortality: Innovative COVID-19 diagnostics and testing strategies - Melodia, Pietro; Stocchi, Manuel; Gentile, Leandro; Odone, Anna; Renzi, Cristina; Signorelli, Carlo (Acta Biomedica Atenei Parmensis, 2023)
Detecting SARS-CoV-2 remains a critical component in the global effort to control COVID-19, particularly with the emergence of variants. Since the outbreak, diagnostic techniques have evolved to meet different contexts and needs. Methods: In this study, we analyzed the use of these techniques in five countries (i.e. Italy, Denmark, the United Kingdom, Sweden, and Israel) based on their specific national testing and contact tracing strategies. We also examined the number of tests performed per week, the positivity rate of tests, and the mortality rate in these populations during the same time periods. These countries were chosen based on the directives of the consortium involved in the CORONADX project.